Rotinas organizacionais: reinventando o conhecimento adquirido através da cooperação - Beltrame, Gabriela (2017)
Cooperation is a strategy used by the companies to develop and stay in the market, and one of their results is that partners can develop a common knowledge base, based on the experience and expertise of both partners. An important advantage of the cooperation is the sharing of knowledge. Provan, Fish and Sydow (2007), analyzed different forms of interactions between individuals in networks. Based on these interactions, it was proposed that knowledge is shared within networks through an actor over another actor, a network over individual actors, individual actors over a network and in all the network or level of network interactions. This new knowledge can be combined with partners' experiences to create new routines as well as resources that provide the basis for sustainable competitive advantage. Routines are considered in the research as repetitive standards of organizational behavior, that are applied at the operational and strategic levels of the organizations. A few studies have been both from the theoretical and empirical point of view that refer to the analysis of this thematic in cooperative processes. This work aims to identify new organizational routines applied by companies that participate in horizontal interorganizational networks, resulting from the knowledge acquired through cooperation. It is believed that this work allows a greater understanding of the results of the cooperative process, showing what really happens in the day to day of these companies after the entry into the network and how they take advantage and change the possibilities and available information and often required by the network and partners to improve the business. To achieve this goal, a qualitative approach was adopted as research method with an exploratory nature by means of the study of multi cases. The units of analysis are ten companies from the central and northwestern regions of the Rio Grande do Sul state, inserted in two Cooperative Networks of the Supermarkets branch. For the data collection, in-depth interviews with the managers of these companies were used and some secondary data were obtained in the websites of the networks. The data were analyzed using the technique of content analysis. The results shown that the companies found through the different cooperation mechanisms to share the knowledge, prevailing the face-to-face meetings of the network and the exchange of e-mail between the members of the network. Among the ways to share knowledge, an actor over another actor, a network over individual actors and the entire network or level of network interactions can be highlighted. However, one of the proposed forms, individual actors on a network, did not generate major impacts for the companies and for the network. These exchanges have to lead to the formation of new organizational routines, which are from the changes between the internal offers and those of the Network, up to the framing of rules imposed by the network, as well as attention to regulatory agencies or the use of software to reduce expenses and to control the internal processes. It should be noted that the new routines were positive for the organizations and according to the managers helped in the growth and development of the companies as well as in the maintenance and permanence in the market. This research brings empirical and theoretical contributions allowing the understanding how the knowledge shared in a network can transform and develop many companies, allowing that small details and simple information can contribute to the growth and to the permanence of these companies in the market.